2018
DOI: 10.1002/jcla.22565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical application of multiple tumor marker protein chip in the diagnostic of lung cancer

Abstract: The C-12 multiple tumor protein-chip detective system has acceptable sensitivity in the diagnostic of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…In our current study, among the lung cancer patients who underwent testing for EGFR mutations, 49.10% had mutations in the younger group, and 44.81% had mutations in the older group; the difference was not significant, which was consistent with a recent study in Chinese patients 46 . CEA is one of the most widely used tumour markers, and elevated CEA expression is often observed in patients with lung cancer, especially those with adenocarcinoma 49 , 50 . SCC has been confirmed to be closely related to the prognosis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In our current study, among the lung cancer patients who underwent testing for EGFR mutations, 49.10% had mutations in the younger group, and 44.81% had mutations in the older group; the difference was not significant, which was consistent with a recent study in Chinese patients 46 . CEA is one of the most widely used tumour markers, and elevated CEA expression is often observed in patients with lung cancer, especially those with adenocarcinoma 49 , 50 . SCC has been confirmed to be closely related to the prognosis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the mean value in lung cancer was 18.49±45.97 (Table 1), but Huaiqian Dou et al [10] reported that the mean in lung cancer was 9.34±13.67. In contrast, Xiaochuan Wang et al [32] reported that it was 28.39±51.91. These differences might be caused by a sampling error, detection kit choice, and instrument differences.…”
Section: Discussionmentioning
confidence: 89%
“…NSE is a type of tumor markers of SCLC, [31] and related studies have shown that plasma Fbg often increases obviously in SCLC patients. [7,24] The mechanisms activating coagulation and fibrinolysis in SCLC patients and NSCLC patients are different.…”
Section: Discussionmentioning
confidence: 99%